PRODUKSI KELAS PREKARIAT OLEH PERGURUAN TINGGI DI INDONESIA - Saktiyanti Jahja, Rusfadia (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2021)
This study describes the social practice of precariat class production carried out by universities in Indonesia. This is different from previous studies which looked more at the practice of social discrimination in precariats (Standing, 2010; Yasih 2019). This study uses a qualitative methodology with in-depth interviews and secondary data analysis on the condition of contract workers in urban areas. This study further explains how universities as educational institutions contribute to the birth of a new precariat. This is then legitimized by various labor regulations and educational curricula which are highly oriented to the needs of the labor market. On the other hand, universities with independent campus curriculum designs must adapt to market tastes, technological developments, and globalization that are wrapped with limited infrastructure..